Assessment of genetic variation among drought tolerant recombinant inbred lines (RILs) of Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
The present study reveals the genetic variation among 225 Recombinant Inbred Lines (RILs) derived from the cross Rohini X PBR-97 which were evaluated under normal and water stress conditions. Significant genetic variation was observed for plant height, main shoot length, fruiting zone length, siliqua length, biological yield/plant, harvest index, seed yield/plant, fibre, phenol, days to flowering under normal conditions while plant height, main shoot length, fruiting zone length, siliqua length, seed/siliqua, harvest index, phenol, days to flowering were found to be significant under drought conditions. Heritability estimates were high (>70%) for main shoot length, siliqua length, seed yield/plant, and phenol content. Seed yield per plant was significantly and positively correlated with plant height (0.37**), main shoot length (0.19*), fruiting zone length (0.16*), siliqua length (0.19*), seeds/siliquae (0.16*), biological yield per plant (0.45**) and harvest index (0.61**) and negatively correlated with oil content (-0.13), fibre (-0.28**). Further, 25 promising RILs were identified based on seed yield/plant which can further be used in brassica improvement breeding programmes to develop drought tolerant brassica varieties.